OWE-04 A capture-recapture study of all-age IBD point prevalence in scotland. Issue 2 (June 2019) - Jones, Gareth-Rhys; Lyons, Mathew; Bisset, Cathy; Plevris, Nikolas; Jenkinson, Philip; Fulforth, James; Kirkwood, Kate; Chuah, Shaun; Minnis, Sarah; Gillespie, Sarah-Louise; Brindle, William; Burgess, Christopher; et al.
Abstract : Background: A recent systematic review reports an overall prevalence for IBD of 0.3% in Western countries 1 but there are no UK estimates since 2003. We aimed to report current all-age prevalence, healthcare usage and forecast 2028 caseload, for IBD in Lothian. Methods: We conducted an extensive capture-recapture search strategy, manually confirming all diagnoses through electronic patient record (EPR) review, to provide point prevalence estimates for Lothian, Scotland (Population 889, 450). Patients were identified from inpatient IBD codes (K50/51/52), IBD pathology codes, IBD biologic prescriptions, primary care mesalazine prescriptions, an existing calprotectin database and a paediatric IBD registry to identify 'possible' IBD cases to 31/08/18. Eight IBD physicians then manually screened the EPR for all possible cases to identify true cases as per Lennard-Jones/Porto criteria. Prevalence was calculated using postcode, date of diagnosis/death and population estimates from National Records Scotland. We then assessed our IBD cohort for attendance at secondary care, IBD-related admission, IBD-drug usage and projected 2028 Lothian IBD prevalence using auto-regressive integrated moving average (ARIMA) modelling. Results: 24, 188 possible IBD case records were manually reviewed to exclude non-IBD cases, leaving 10, 866 true positives (figure 1A). The point prevalence of IBD in Lothian on 31/8/18 was 0.78% (figure 1A). 43.8% of prevalent cases attended out-patient clinic over the preceding 3 years which was inversely correlated with increasing age (Mean age 46.7±0.3 in follow up versus 54.9±0.3 not in follow up, p<0.0001)(figure 1B). Follow-up was significantly associated with IBD-related admission (OR 5.7 4.6–6.9, p<0.0001) and IBD-related admission duration was positively correlated with increasing age (R 2 =0.02, slope=0.12 0.09–0.15, p<0.0001). ARIMA modelling projects a point prevalence on 01/08/28 of 0.99% (0.94–1.04%) affecting 1.6% (1.5–1.7%) of the >50s who will account for 59% of prevalent IBD. Conclusions: The prevalence of IBD in the UK is 0.78% (1 in 125 individuals). This is much higher than previously reported, and will continue to rise due to compound prevalence, reaching >1.0% by the end of 2028. Reference: Siew Ng, et al. Worldwide incidence and prevalence of inflammatory bowel disease in the 21st century: a systematic review of population-based studies. Lancet 2018;390:pp2769–2778.